Learning Strategy at SD Muhammadiyah 2 Reinforcement Amid the Covid-19 Pandemic - Jihan Iffa Suroiya; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine learning strategies in elementary schools during the Covid-19 pandemic, especially at Muhammadiyah 2 Tulangan Elementary School. This study applies a descriptive technique, namely knowing social problems and analyzing to find out complex descriptions and qualitative information that comes from information sources around. The results of the research through interviews, documentation and observations on learning strategies carried out at SD Muhammadiyah 2 Tulangan during the Covid-19 pandemic, showed that the learning process through online learning was going well even though there were several challenges faced.